HUBUNGAN POLA ASUH IBU TERHADAP PERKEMBANGAN SOSIAL ANAK PRA SEKOLAH DI KELOMPOK BERMAIN BUNAYYA PEKANBARU TAHUN 2018 - Hamidah Sari Batubara; Rika Sri Wahyuni; Dina Apriani Adha (Ensiklopedia of Journal, 2019)
Preschoolers are an individual development phase of about 2-6 years, some physical development in preschoolers. Parents are the main role takers in nurturing their children. Parenting patterns of parenting are patterns of behavior that parents use to connect with children. The formulation of the problem from this research is "Is There a Relationship Pattern of Parenting Mother Against Social Development Of Pre-School Children In Playing Group Bunayya Pekanbaru Year 2018". This study aims to "Relationship Patterns Mother Mother Against Social Development Pre-School Children In Playing Group Bunayya Pekanbaru Year 2018". This research is quantitative with analytic design using cross sectional. Carried out on 12 March - 13 march 2018 in group play bunayya pekanbaru. Number of study population counted 25 people with sample counted 25 people by using total population technique. Instrument of this research use questioner, data processing done univariat which presented in frequency table form, followed by bivariate analysis using software SPSS vs. 20, then presented descriptively and analitic through statistic test. The result showed that the majority of mothers used democratic parenting as many as 15 respondents (60%) had normal child social development as many as 21 children (84%). From the results of chi.square test known not significant relationship between mother's parenting pattern with the social development of preschool children in Playing Group Bunayya Pekanbaru Year 2018. Through this research is expected to the mother to further optimize in raising children by using good parenting patterns for children and paying attention to the social development of children according to the age of the child.